The Bus Arrival Information System for Tunanetra Based on Firebase Cloud Messaging and Google Text to Speech - Guruh Aryotejo; Ahmad Syarifuddin Hidayatulloh; Mufadhol Mufadhol (Journal of Applied Informatics and Computing, 2020)
Buses are one of the means of public transportation and there are also services provided by the Government to the community and their construction must meet standards so that the community can use them. Bus-type public transportation in the city of Semarang only stops at every bus stop. The current problem is that bus stops in the city of Semarang are not friendly to people with disabilities, especially for blind people. They have to wait for the bus to arrive then ask people around the identity of the bus that is coming. This study aims to build a bus arrival information system using a combination of Arduino Uno, Raspberry Pi 3B, LCD, nRF24L01 module, LED, Speaker, Google Text to Speech and Firebase Cloud Messaging. We perform the simulation by analyzing the transceiver connectivity on the bus to the information system transceiver and providing the obstacles in between. In addition, we also tested the maximum distance of the transceiver device on the bus stop connected to the router. Furthermore, the information systems usage time at bus stops using various power banks was also tested. We found that the transceiver on the bus and the information system transceiver was connected to a maximum distance of 40 meters and was not affected by rainy weather. In addition, the system execution time is highly dependent on the internet connection used on the information system transceiver. Meanwhile, the maximum distance between the information system and the router is also very dependent on the transceiver capability of the router and the information system. Furthermore, the time to use the information system using the Power Bank indicates that the greater the power bank, the longer the information system will be used. This shows that this system is suitable for use by the blind in using public transportation and becomes the basis for research in helping the blind.